Umbilical cord blood–derived exosomes from healthy term pregnancies protect against hyperoxia‐induced lung injury in mice - Xin‐qi Zhong; Ding Wang; Shuang Chen; Jing Zheng; Tao‐fang Hao; Xiu‐hong Li; Li‐hua Luo; Jian Gu; Chang‐yu Lian; Xiao‐sa Li; Dun‐jin Chen (Clinical and Translational Science, 2023)
Abstract Bronchopulmonary dysplasia (BPD) is a chronic, devastating disease primarily occurring in premature infants. To date, intervention strategies to prevent or treat BPD are limited. We aimed to determine the effects of umbilical cord blood‐derived exosomes (UCB‐EXOs) from healthy term pregnancies on hyperoxia‐induced lung injury and to identify potential targets for BPD intervention. A mouse model of hyperoxia‐induced lung injury was created by exposing neonatal mice to hyperoxia after birth until the 14th day post birth. Age‐matched neonatal mice were exposed to normoxia as the control. Hyperoxia‐induced lung injury mice were intraperitoneally injected with UCB‐EXO or vehicle daily for 3 days, starting on day 4 post birth. Human umbilical vein endothelial cells (HUVECs) were insulted with hyperoxia to establish an in vitro model of BPD to investigate angiogenesis dysfunction. Our results showed that UCB‐EXO alleviated lung injuries in hyperoxia‐insulted mice by reducing histopathological grade and collagen contents in the lung tissues. UCB‐EXO also promoted vascular growth and increased miR‐185‐5p levels in the lungs of hyperoxia‐insulted mice. Additionally, we found that UCB‐EXO elevated miR‐185‐5p levels in HUVECs. MiR‐185‐5p overexpression inhibited cell apoptosis, whereas promoted cell migration in HUVECs exposed to hyperoxia. The luciferase reporter assay results revealed that miR‐185‐5p directly targeted cyclin‐dependent kinase 6 (CDK6), which was downregulated in the lungs of hyperoxia‐insulted mice. Together, these data suggest that UCB‐EXO from healthy term pregnancies protect against hyperoxia‐induced lung injuries via promoting neonatal pulmonary angiogenesis partially by elevating miR‐185‐5p.